Catalytic decomposition of 2 methanol in methane over metallic catalyst by fixed-bed catalytic reactor - Awad, A. (MDPI AG, 2021)
The structure and performance of promoted Ni/Al2O3 with Cu via thermocatalytic decomposition (TCD) of CH4 mixture (2 CH3OH) were studied. Mesoporous Cat-1 and Cat-2 were synthesized by the impregnation method. The corresponding peaks of nickel oxide and copper oxide in the XRD showed the presence of nickel and copper oxides as a mixed alloy in the calcined catalyst. Temperature program reduction (TPR) showed that Cu enhanced the reducibility of the catalyst as the peak of nickel oxide shifted toward a lower temperature due to the interaction strength of the metal particles and support. The impregnation of 10 Cu on Cat-1 drastically improved the catalytic performance and exhibited 68 CH4 conversion, and endured its activity for 6 h compared with Cat-1, which deactivated after 4 h. The investigation of the spent carbon showed that various forms of carbon were obtained as a by-product of TCD, including graphene fiber (GF), carbon nanofiber (CNF), and multi-wall carbon nanofibers (MWCNFs) on the active sites of Cat-2 and Cat-1, following various kinds of growth mechanisms. The presence of the D and G bands in the Raman spectroscopy confirmed the mixture of amorphous and crystalline morphology of the deposited carbon. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.